The role of ecodesign in circular economy to improve the performance of enterprises in the fashion industry: a systematic review of literature - Jochamowitz Yriberry, Michelle (2023)
High rates of contamination found in the fashion industry call for actions to change their linear model-based production activities. The transition to a circular economy using ecodesign as a tool entails challenges and constraints to attain the benefits of an improved business performance. The aim of this article is to identify the impact of including ecodesign as a tool of circular economy for improved performance in fashion businesses, analyzing the existing literature from 2013 to 2021 through a systematic literature review (SLR). Results show that ecodesign is a pillar that favors the achievement of circular economy thanks to the design of more sustainable products that can return to the production cycle and/or be recycled so as to reduce environmental impacts from the first stage of their life cycle. In addition, methodologies and tools driving companies toward ecodesign were identified. Successful ecodesign application influences business performance leading to an improved energy and resource efficiency in processes, reduced costs, and higher profitability. Achieving this requires the engagement of all the parties involved in the value chain. Thus, businesses may achieve a competitive advantage, improve their brand value, and attain a better customer satisfaction.